MASTERING THE MINERAL WATER MARKET: LE MINERALE SUCCESSFUL STRATEGY IN WINNING CONSUMERS HEARTS - Firdaus , Dafa Akbar Anugrah; Febriansah , Rizky Eka; Pebrianggara, Alshaf (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
General Background: Global warming and environmental damage are critical issues exacerbated by the use of non-environmentally friendly products. Specific Background: Le Minerale, a bottled water brand, is integrating green promotion, product innovation, and brand image to influence consumer behavior, highlighting the importance of studying their impact on purchasing decisions. Knowledge Gap: Despite the growing trend in sustainable marketing, limited research exists on how these specific factors affect consumer purchasing decisions for environmentally friendly products, particularly in the bottled water sector in Indonesia. Aims: This study aims to determine the role of green promotion, product innovation, and brand image on purchasing decisions for Le Minerale products in Sidoarjo, Indonesia. Results: Using a sample of 100 respondents, multiple linear regression analysis revealed that all three variables—green promotion, product innovation, and brand image—significantly and positively influence purchasing decisions. Novelty: The research highlights the direct link between green promotion campaigns and consumer decisions, emphasizing the importance of product innovation, particularly eco-friendly packaging, in enhancing brand image and driving purchase behavior. Implications: These findings suggest that environmentally conscious marketing strategies not only contribute to positive brand perceptions but also influence consumer choices in favor of sustainable products. Future research could expand the geographical scope and explore additional variables, such as price perception and product quality, to further understand purchasing behavior in different contexts.